Metagenomic next-generation sequencing may assist diagnosis of cat-scratch disease - Li, Mingxia; Yan, Kunli; Jia, Peisheng; Wei, Erhu; Wang, Huaili (Frontiers in Cellular and Infection Microbiology, 2022)
Bartonella henselae, the pathogen that causes cat-scratch disease (CSD), is relatively rare in the clinic. CSD usually causes mild clinical manifestations, which self-heal in a matter of weeks. However, in immunocompromised patients, CSD may cause systemic disorders that can lead to critical illness. Due to the diversity of symptom signs and the lack of a golden standard for diagnosis, identifying atypical CSD in a timely manner presents a challenge. Metagenomic next-generation sequencing (mNGS), is a promising technology that has been widely used in the detection of pathogens in clinical infectious diseases in recent years. mNGS can detect multiple pathogens quickly and accurately from any given source. Here, we present a case of atypical CSD, which was diagnosed using mNGS. The patient manifested a fever of unknown infectious origin, and routine antibiotic treatment was ineffective. mNGS was employed to test the patient’s peripheral blood, which led to the detection of B. henselae. This was rarely seen in previous CSD reports. We surmised that the patient presented with atypical CSD and thus a targeted therapy was recommended. Crucially, the patient recovered rapidly. Based on this case study findings, we recommend that CSD should be included in the differential diagnosis for fever of unknown origin and that mNGS may be helpful in the diagnosis of CSD.